2003
DOI: 10.1017/s1357729800053601
|View full text |Cite
|
Sign up to set email alerts
|

Feeding patterns, growth performance and carcass traits in group-housed growing-finishing pigs: the effect of terminal sire line, halothane genotype and age

Abstract: The effects of terminal sire line, halothane genotype and age on feeding patterns and growth performance were studied in 208 castrated growing-finishing pigs distributed in two batches. In batch 1 (no. = 130), pigs came from crosses of NN Landrace × Large White sows with a Pietrain Nn (Pi-Nn) or a Large White ✕ Pietrain Nn terminal sire line (LwPi-Nn). In batch 2 (no. = 78), the same sows were used but crossed with three different terminal sire lines : a Pietrain nn (Pi-nn), and two Pietrain NN (Pi-NNa and Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…These results confirm those of previous studies (Edwards, Bates, & Osburn, 2003;Edwards et al, 2006;Gispert et al, 2007), which reported higher backfat thickness in Duroc-sired progeny compared to Pietrain-or Large White-Pietrain-sired progeny (Fàbrega et al, 2003). On the other hand, the low backfat thickness observed in the MS-115×MO pigs is due to their low slaughter weight, since following Adjusted for similar ADFI.…”
Section: Growth Performance and Carcass Traitssupporting
confidence: 90%
See 2 more Smart Citations
“…These results confirm those of previous studies (Edwards, Bates, & Osburn, 2003;Edwards et al, 2006;Gispert et al, 2007), which reported higher backfat thickness in Duroc-sired progeny compared to Pietrain-or Large White-Pietrain-sired progeny (Fàbrega et al, 2003). On the other hand, the low backfat thickness observed in the MS-115×MO pigs is due to their low slaughter weight, since following Adjusted for similar ADFI.…”
Section: Growth Performance and Carcass Traitssupporting
confidence: 90%
“…Terminal sire line Embrapa MS-115 contains a 62.5% proportion of Pietrain breed, and as demonstrated in earlier studies, this breed and its progeny have a low feed intake and, consequently, slower growth rate and lower final weight at a given age than other breeds such as Duroc and Large White and their progenies (Augspurger et al, 2002;Bertol et al, 2010;Edwards et al, 2006;Fàbrega et al, 2003;Gispert et al, 2007). Hence, this is probably the reason why the progeny of the terminal sire line Embrapa MS-115 displayed a lower growth performance compared with the Duroc progeny.…”
Section: Growth Performance and Carcass Traitsmentioning
confidence: 76%
See 1 more Smart Citation
“…The average EST during the night was 34.84 ± 0.79 • C and during the day 32.80 ± 1.0 • C ( Figure 6); while the behavior in the ambient temperature is the reverse: the average of the medians during the day was 23. 22 3.2. Animal Temperature Figure 7 represents the average temperature and the standard deviation of each of the animals monitored.…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with Bigelow and Houpt (1988), studies on feeding patterns in pigs showed in general an increase in feed intake, meal size and feeding rate, and a decrease or varying trend in meal frequency, meal duration, and feeding time when pigs gained weight (e.g. Fàbrega et al, 2003;Hyun et al, 1997;Nienaber et al, 1990;Walker, 1991).…”
Section: Discussionmentioning
confidence: 70%